ANALISIS PENGARUH VARIABEL PEMBIAYAAN MODAL, LAMA USAHA SERTA MODAL SENDIRI TERHADAP PENDAPATAN ANGGOTA PELAKU UMKM - Kusumajaya, Robby Andika; Qoriah, Shinta Dewi (MANAJEMEN, 2023)
As a sharia microfinance institution that has a function as developing productive businesses and investments to improve the quality of micro, small and medium enterprises, this study aims to examine the effect of variable capital financing, length of business and own capital on the income of customers who are members of the Sharia Financing Savings and Loans Cooperative Baitul Mal wa Tamwil Nurul Barokah Klego branch, Boyolali regency. They are micro, small and medium enterprises (MSMEs), the population in this study is 108 with a sample of 52 respondents. Analysis techniques use multivariate regression analysis and use instrument tests which include validity and reliability tests, and descriptive statistical tests of respondents based on sex, based on age, and classical assumption tests include normality tests, multicolleniarity tests, heterokedasticity tests, and multiple linear regression analysis and model permanence tests including coefficients of determination, and hypothesis testing includes t tests, F tests. The results showed that only own capital had a positive effect on MSME income, while capital financing and long time did not affect MSME income, because financing members often took advantage of capital loans not in accordance with loan agreements and lack of innovation to see consumer interest so that it stagnated.